Oscillatory autophagy induction is enabled by an updated AMPK-ULK1 regulatory wiring - Kapuy, Orsolya; Holczer, Marianna; Csabai, Luca; Korcsmáros, Tamás (PLOS ONE, 2024)
Autophagy-dependent survival relies on a crucial oscillatory response during cellular stress. Although oscillatory behaviour is typically associated with processes like the cell cycle or circadian rhythm, emerging experimental and theoretical evidence suggests that such periodic dynamics may explain conflicting experimental results in autophagy research. In this study, we demonstrate that oscillatory behaviour in the regulation of the non-selective, stress-induced macroautophagy arises from a series of interlinked negative and positive feedback loops within the mTORC1-AMPK-ULK1 regulatory triangle. While many of these interactions have been known for decades, recent discoveries have revealed how mTORC1, AMPK, and ULK1 are truly interconnected. Although these new findings initially appeared contradictory to established models, additional experiments and our systems biology analysis clarify the updated regulatory structure. Through computational modelling of the autophagy oscillatory response, we show how this regulatory network governs autophagy induction. Our results not only reconcile previous conflicting experimental observations but also offer insights for refining autophagy regulation and advancing understanding of its mechanisms of action.